Death of a laken ; Better than nothing ; The Perfect alternative [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
A deadly pollutant killed over a million pesos worth of fish in Laguna de Bay. The multigrade system of education brings together first second and third grader under one classroom. Tackles one of the fastest singing band in Manila.